PP2Acα-B′/PR61 Holoenzyme of Toxoplasma gondii Is Required for the Amylopectin Metabolism and Proliferation of Tachyzoites - Mingxiu Zhao; Yi Yang; Yue Shi; Xueqiu Chen; Yimin Yang; Lingtao Pan; Zhendong Du; Hongchao Sun; Chaoqun Yao; Guangxu Ma; Aifang Du (Microbiology Spectrum, 2023)
ABSTRACT Here, we report that the inhibition of the PP2A subfamily by okadaic acid results in an accumulation of polysaccharides in the acute infection stage (tachyzoites) of Toxoplasma gondii, which is a protozoan of global zoonotic importance and a model for the apicomplexan parasites. The loss of the catalytic subunit α of PP2A (ΔPP2Acα) in RHΔku80 leads to the polysaccharide accumulation phenotype in the base of tachyzoites as well as residual bodies and significantly compromises the intracellular growth in vitro and the virulence in vivo. A metabolomic analysis revealed that the accumulated polysaccharides in ΔPP2Acα are derived from interrupted glucose metabolism, which affects the production of ATP and energy homeostasis in the T. gondii knockout. The assembly of the PP2Acα holoenzyme complex involved in the amylopectin metabolism in tachyzoites is possibly not regulated by LCMT1 or PME1, and this finding contributes to the identification of the regulatory B subunit (B′/PR61). The loss of B′/PR61 results in the accumulation of polysaccharide granules in the tachyzoites as well as reduced plaque formation ability, exactly the same as ΔPP2Acα. Taken together, we have identified a PP2Acα-B′/PR61 holoenzyme complex that plays a crucial role in the carbohydrate metabolism and viability in T. gondii, and its deficiency in function remarkably suppresses the growth and virulence of this important zoonotic parasite both in vitro and in vivo. Hence, rendering the PP2Acα-B′/PR61 holoenzyme functionless should be a promising strategy for the intervention of Toxoplasma acute infection and toxoplasmosis. IMPORTANCE Toxoplasma gondii switches back and forth between acute and chronic infections, mainly in response to host immunologic status, which is characterized by flexible but specific energy metabolism. Polysaccharide granules are accumulated in the acute infection stage of T. gondii that have been exposed to a chemical inhibitor of the PP2A subfamily. The genetic depletion of the catalytic subunit α of PP2A leads to this phenotype and significantly affects the cell metabolism, energy production, and viability. Further, a regulatory B subunit PR61 is necessary for the PP2A holoenzyme to function in glucose metabolism and in the intracellular growth of T. gondii tachyzoites. A deficiency of this PP2A holoenzyme complex (PP2Acα-B′/PR61) in T. gondii knockouts results in the abnormal accumulation of polysaccharides and the disruption of energy metabolism, suppressing their growth and virulence. These findings provide novel insights into cell metabolism and identify a potential target for an intervention against a T. gondii acute infection.